Kajian Kebutuhan Modal, Sumber Modal, dan Tingkat Pengembalian Modal Usahatani Padi Sawah di Desa Kasumeia Kecamatan Onembute Kabupaten Konawe - Suharjo Suharjo; Abu Rahman; Muhammad Sidiq Al-Fajar (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2022)
Sources of capital in farming come from the farmers themselves or outside the farmers. Sources of capital originating from farmers themselves come from savings or the results of their farming income. In contrast, those deriving from outside the farmers come from creditors (lenders) from moneylenders, cooperatives, banks or other financial institutions. In general, for most of the problems farmers face, tiny farmers cannot finance their farming using their funds. However, to provide capital assistance. However, these efforts cannot fully overcome the capital difficulties for farmers. This study aims to analyze the capital requirements of each lowland rice farmer, analyze the sources and methods of lowland rice farmers' capital, and analyze the ability of farmers to repay capital loans in Kasumeia Village, Onembute District, Konawe Regency. The study was carried out in Kasumeia Village, Oneembute District, Konawe Regency, from June to July 2021. The variables observed in this study are 1. The identity of respondent farmers includes age, education, farming experience, and the number of dependents in the family. 2. Farming conditions include sources of capital, amount of capital, area of arable land, production facilities (seeds, fertilizers, pesticides), labour, prices of production facilities, production prices, and equipment used. Data analysis in this study was carried out using qualitative research and analysis of the rate of return on capital. The results showed that 1 The number of capital farmers need to manage their farming business is Rp. 11,936,935/ha. 2. Farmers' sources of capital mostly come from their capital (73.33%), while the rest is obtained from bank loans and cooperatives (26.67%). 3. The ability of farmers to pay back capital is relatively low (ROI of 0.8).